2010
DOI: 10.1038/nature08643
|View full text |Cite
|
Sign up to set email alerts
|

A large coronal loop in the Algol system

Abstract: The close binary Algol system contains a radio-bright KIV subgiant star in a very close (0.062 astronomical units) and rapid (2.86 day) orbit with a main sequence B8 star. Because the rotation periods of the two stars are tidally locked to the orbital period, the rapid rotation drives a magnetic dynamo. A large body of evidence points to the existence of an extended, complex coronal magnetosphere originating at the cooler K subgiant. The detailed morphology of the subgiant's corona and its possible interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
41
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 27 publications
5
41
0
Order By: Relevance
“…However, in the framework of the two polar lobe model (Favata et al 2000, Retter et al 2005, Peterson et al 2010 for the site of the quiescent corona, one could imagine that the absorption column density is highest in or around those lobes, where the quiescent corona is dominating. It is reduced towards the equatorial regions, at which the certainly non-polar flare of this XMM-Newton observation is located.…”
Section: Cool Absorbing Gas Surrounding the K Starmentioning
confidence: 99%
“…However, in the framework of the two polar lobe model (Favata et al 2000, Retter et al 2005, Peterson et al 2010 for the site of the quiescent corona, one could imagine that the absorption column density is highest in or around those lobes, where the quiescent corona is dominating. It is reduced towards the equatorial regions, at which the certainly non-polar flare of this XMM-Newton observation is located.…”
Section: Cool Absorbing Gas Surrounding the K Starmentioning
confidence: 99%
“…It is likely that the radio emission originates in active regions, e.g., magnetic-loop structures, approximately a stellar radius in size (see, e.g., Peterson et al 2010;Mullan et al 2006;Franciosini et al 1999;Lestrade et al 1988), which are rooted on the surface of the star. Indeed, IM Peg is of the spectral type K2, and Mullan et al (2006) show that the largest coronal loops, with sizes up to two stellar radii, occur in stars of type K2 or later.…”
Section: Rapid Evolution Of the Radio Structurementioning
confidence: 99%
“…However, the emission region is often extended by as much as the separation between the two stars (∼2 mas), which leads to the question: is there any correlation between the geometry of the emission region and the orbital phase? For example, a correlation of the amount and/or angle of elongation of the radio emission with orbital phase might be expected if the radio emission originates predominantly along the line between the two stars (as is seen in the Algol system; Peterson et al 2010; although we note that, unlike IM Peg, Algol is an interacting system for which emission predominately from within the region In each case where the total flux density did not vary discernibly within the observing interval or where the flux density was determined from VLBI rather than VLA observations, the observational uncertainty (1σ ) is shown by a dotted error bar centered on the dot; the fractional observational uncertainties for the other sessions are similar. Right panel: the same flux densities, but plotted against orbital phase (using the orbital parameters of Marsden et al 2005).…”
Section: Orientation and Elongation Of The Radio Emission Regionmentioning
confidence: 99%
“…Recently, Peterson et al (2010) presented high-resolution radio images of the Algol binary system resolving a large coronal loop reaching from one to the other pole of the K giant secondary, being orientated towards the primary B star. The authors modeled the radio emission observed from this loop by assuming synchrotron emission from an electron population with a homogeneous density of n e = 10 −3 electrons/cm −3 and a power-law spectrum so that n(E) = n e (E/E min ) −3/2 where E min = 80 keV.…”
Section: Electron Collisional Excitationmentioning
confidence: 99%